Hoofdbestuur met zittend v.l.n.r. Kroon, Pot, Kruithof, Kwakkel en De Kleine. Staande v.l.n.r. V.d. Linde, Sluiter, Anbeek en Fin (1939)
Hoofdbestuur met zittend v.l.n.r. Kroon, Pot, Kruithof, Kwakkel en De Kleine. Staande v.l.n.r. V.d. Linde, Sluiter, Anbeek en Fin.